Identification of key aroma compounds and formation of sensory properties incooked indica rice - GUAN Lina; YE Guodong; ZHANG Min; LI Sixuan (浙江大学学报. 农业与生命科学版)
Taking indica rice as the research object, solid phase micro-extraction (SPME) and solvent-assisted flavor evaporation (SAFE) coupled with gas chromatography-olfactory-mass spectrometry (GC-O-MS) were applied to identify and characterize the aroma compounds in cooked rice. The key aroma components of cooked rice were further identified through quantitative analysis, odor activity value (OAV), and aroma recombination and omission experiments. The results showed that a total of 49 aroma compounds were identified, among which 2-methylbutanal, hexanal, 2-pentylfuran, nonanal, 1-octen-3-ol, (E)-2-nonenal, (E)-2-decenal, acetoin, 2(5H)-furanone, and 2-acetyl-1-pyrroline were screened out as the key aroma compounds. Seven sensory characteristics of cooked rice were evaluated using sensory quantitative descriptive analysis, namely cooked grain, nutty, grassy, caramel, sweet, fruity, and floral aromas. Partial least squares regression (PLSR) analysis showed that 2-methylbutanal, 2-pentylfuran, and 2(5H)-furanone were related to the formation of nutty and sweet sensory attributes; hexanal, (E)-2-nonenal, (E)-2-decenal, 2-methoxy-4-vinylphenol and indole were related to grassy and floral aromas; nonanal and decanal were related to fruity aroma; and 2-acetyl-1-pyrroline was significantly correlated with caramel aroma. Cooked grain aroma, an important sensory attribute of cooked rice, had a significantly positive correlation with various aroma compounds. This study provides a scientific basis for the regulation of cooked rice flavor and the construction of a sensory quality evaluation system.